2020
DOI: 10.3389/fvets.2020.00441
|View full text |Cite
|
Sign up to set email alerts
|

The Three Flagellar Loci of Brucella ovis PA Are Dispensable for Virulence in Cellular Models and Mice

Abstract: Brucella ovis is a facultative intracellular bacterium that causes a non-zoonotic ovine brucellosis mainly characterized by male genital lesions and is responsible for important economic losses in sheep farming areas. Studies about the virulence mechanisms of Brucella have been mostly performed with smooth (bearing O-polysaccharide in lipopolysaccharide) zoonotic species, and those performed with B. ovis have revealed similarities but also relevant differences. Except for few strains recently isolated from unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Nevertheless, this observation is not in disagreement with the proposed role of MucR as repressor of ftcR since the predicted binding site of FtcR upstream of fliF ( 42 ) is missing in B. ovis due to two independent deletion events accounting for 283 bp ( 11 ). Even if there was a MucR-mediated regulation of flagellar gene expression in B. ovis PA, deletion of mucR would not have a relevant impact in flagellum-dependent bacterial properties since it has been demonstrated that the entire three main flagellar loci are dispensable for B. ovis PA virulence, and their deletion does not modify any of the evaluated bacterial characteristics ( 15 ). Upregulation of flagellar genes detected in B. canis RM6/66 Δ mucR ( 32 ) was also in accordance with the results described for the B. melitensis 16M mutant ( Table 4 ), but the expression of flagellar genes in B. abortus 2308 does not seem to be dependent on MucR ( 20 ) ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, this observation is not in disagreement with the proposed role of MucR as repressor of ftcR since the predicted binding site of FtcR upstream of fliF ( 42 ) is missing in B. ovis due to two independent deletion events accounting for 283 bp ( 11 ). Even if there was a MucR-mediated regulation of flagellar gene expression in B. ovis PA, deletion of mucR would not have a relevant impact in flagellum-dependent bacterial properties since it has been demonstrated that the entire three main flagellar loci are dispensable for B. ovis PA virulence, and their deletion does not modify any of the evaluated bacterial characteristics ( 15 ). Upregulation of flagellar genes detected in B. canis RM6/66 Δ mucR ( 32 ) was also in accordance with the results described for the B. melitensis 16M mutant ( Table 4 ), but the expression of flagellar genes in B. abortus 2308 does not seem to be dependent on MucR ( 20 ) ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The microbiological procedures were reviewed and approved by the Biosecurity Committee of the University of Salamanca, Spain. For non-polar deletion of mucR in B. ovis PA, the wildtype chromosomal gene was replaced by the inactivated gene, following a procedure previously described (11,15). Briefly, two PCR reactions were performed to amplify the 5 ′ and 3 ′ ends of mucR, together with about 700 bp located upstream or downstream the gene, respectively.…”
Section: Cloning Vectors Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brucella has a full set of genes coding for proteins that are assembled into functional flagella, but not all coding genes are expressed ( Delvecchio et al, 2002 ). In some virulent strains of Brucella , fully formed flagella can be observed ( Sidhu-Muñoz et al, 2020 ). Therefore, T4SS and flagella may play a regulatory role together in Brucella ( Delrue et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…pilH is embedded in an operon along with pilG , pilI , and pilJ 84 . The same applies for the flagellar proteins fliE, fliG, fliI, fliJ, fliM, fliN and more 85 .…”
Section: Resultsmentioning
confidence: 99%